The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1758-2229.2010.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, transmission and persistence of Escherichia coli in a cohort of mothers and their infants

Abstract: Despite that Escherichia coli is one of the most important bacteria in early infant colonization and immune modulation, we have limited knowledge about diversity, transmission and persistence within human populations for this bacterium. Here we have utilized a novel, growth-independent, direct typing approach to describe E. coli mother-to-child transmission and persistence within infants in a well-defined cohort of 86 mothers and their infants in Norway. Seven gene multilocus sequence typing of 28 study isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 40 publications
1
36
0
1
Order By: Relevance
“…We have shown that our assay is highly reproducible, with a detection threshold of 10 5 CFU/g of feces; this corresponds to 0.1% of the E. coli population, much lower than the 10% threshold obtained by other methods (20,21,23,26,29). Previous studies picked 20 to 30 isolates from an agar plate per individual and used a semiquantitative method of assessment (20,23,25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that our assay is highly reproducible, with a detection threshold of 10 5 CFU/g of feces; this corresponds to 0.1% of the E. coli population, much lower than the 10% threshold obtained by other methods (20,21,23,26,29). Previous studies picked 20 to 30 isolates from an agar plate per individual and used a semiquantitative method of assessment (20,23,25).…”
Section: Discussionmentioning
confidence: 99%
“…New approaches are therefore needed to improve the sensitivity of detection. The detection of fecal strains present at low frequencies is necessary to understand within-individual fluctuations in strain composition that can be observed over time (18,20,28,29).To obtain insights into the population structure of E. coli in its primary habitat, we assessed the relative proportions of the main E. coli phylogenetic groups in the stools of 100 healthy human subjects; their intestinal microbiota had undergone minimal pathological and medical perturbations. A new, rapid, and sensi-…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing for enterovirus, picornavirus and E.coli as well as other bacterial species will be done as earlier published Witsø et al, 2006Witsø et al, , 2007Muinck et al, 2011). Deep sequencing will be performed on at 454 machines at the Centre for Ethological and Evolutional Sciences (CEES), Institute of Biology, University of Oslo according to the manufacture instructions.…”
Section: Sequencingmentioning
confidence: 99%
“…[23] There is evidence for maternal-infant transmission of gut E. coli. [24] Infants of mothers with atopic dermatitis (who are at genetic risk for atopic dermatitis) are born with meconium that is enriched for Enterobacteriaceae. [25] It is conceivable then that the Enterobacteriaceae can be transmitted in utero and that higher abundance of gut Enterobacteriaceae soon after birth is an early biomarker for atopic dermatitis and subsequent food sensitization.…”
mentioning
confidence: 99%